Implications of trimethylamine N-oxide (TMAO) and Betaine in Human Health: Beyond Being Osmoprotective Compounds - Ilyas, Ashal; Wijayasinghe, Yasanandana Supunsiri; Khan, Ilyas; El Samaloty, Nourhan M.; Adnan, Mohd; Dar, Tanveer Ali; Poddar, Nitesh Kumar; Singh, Laishram R.; Sharma, Hemlata; Khan, Shahanavaj (Frontiers in Molecular Biosciences, 2022)
Osmolytes are naturally occurring small molecular weight organic molecules, which are accumulated in large amounts in all forms of life in order to maintain the stability of cellular proteins and hence preserve their functions during adverse environmental conditions. Trimethylamine-N-oxide (TMAO) and N, N, N-trimethylglycine (betaine) are methylamine osmolytes that have been extensively studied for their diverse roles in humans and have demonstrated opposing relations with human health. Both these osmolytes are obtained from food and also synthesized endogenously using dilatory constituents like choline, carnitine. Especially, gut microbiota plays a vital role in TMAO synthesis and thereby contributes significantly to plasma TMAO levels. The elevated plasma TMAO has been reported to be correlated with the pathogenesis of several human diseases, including cardiovascular disease, heart failure, kidney diseases, metabolic syndrome, etc. and hence TMAO has been recognized as a novel biomarker for the detection/prediction of a number of diseases. In contrast, betaine acts as a methyl donor in one-carbon metabolism, maintain cellular S-adenosylmethionine levels and protects the cells from deleterious effects of increased plasma homocysteine. Betaine also demonstrates antioxidant and anti-inflammatory activities and has a promising therapeutic value in several diseases, including homocystinuria and fatty liver disease. The present review examines the multifarious functions of TMAO and betaine with possible molecular mechanisms towards better understanding of their emerging and diverging functions with probable implications in prevention, diagnosis and treatment of human diseases.